Clinical evidence of acupuncture and moxibustion for irritable bowel syndrome: A systematic review and meta-analysis of randomized controlled trials - Yang, Yuanming; Rao, Kehan; Zhan, Kai; Shen, Min; Zheng, Huan; Qin, Shumin; Wu, Haomeng; Bian, Zhaoxiang; Huang, Shaogang (Frontiers in Public Health, 2022)
Background Acupuncture and moxibustion have been widely used in the treatment of Irritable Bowel Syndrome (IBS). But the evidence that acupuncture and moxibustion for IBS reduction of symptom severity and abdominal pain, and improvement of quality of life is scarce. Methods PubMed, Embase, Cochrane Library, Web of Science, Chinese National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), Wanfang Database, China Biomedical Literature Service System (SinoMed), and unpublished sources were searched from inception until June 30, 2022. The quality of RCTs was assessed with the Cochrane Collaboration risk of bias tool. The strength of the evidence was evaluated with the Grading of Recommendations Assessment, Development and Evaluation system (GRADE). Trial sequential analysis (TSA) was conducted to determine whether the participants in the included trials had reached optimal information size and whether the cumulative data was adequately powered to evaluate outcomes. Results A total of 31 RCTs were included. Acupuncture helped reduce the severity of symptoms more than pharmaceutical drugs (MD, −35.45; 95% CI, −48.21 to −22.68; I2 = 71%). TSA showed the cumulative Z score crossed O'Brien-Fleming alpha-spending significance boundaries. Acupuncture wasn't associated with symptom severity reduction (SMD, 0.03, 95% CI, −0.25 to 0.31, I2 = 46%), but exhibited therapeutic benefits on abdominal pain (SMD, −0.24; 95% CI, −0.48 to −0.01; I2 = 8%) compared to sham acupuncture. Moxibustion show therapeutic benefits compared to sham moxibustion on symptom severity (SMD, −3.46, 95% CI, −5.66 to −1.27, I2 = 95%) and abdominal pain (SMD, −2.74, 95% CI, −4.81 to −0.67, I2 = 96%). Acupuncture (SMD, −0.46; 95% CI, −0.68 to −0.24; I2 = 47%) and the combination of acupuncture and moxibustion (SMD, −2.00; 95% CI, −3.04 to −0.96; I2 = 90%) showed more benefit for abdominal pain compared to pharmacological medications as well as shams. Acupuncture (MD, 4.56; 95% CI, 1.46–7.67; I2 = 79%) and moxibustion (MD, 6.97; 95% CI, 5.78–8.16; I2 = 21%) were more likely to improve quality of life than pharmaceutical drugs. Conclusion Acupuncture and/or moxibustion are beneficial for symptom severity, abdominal pain and quality of life in IBS. However, in sham control trials, acupuncture hasn't exhibited robust and stable evidence, and moxibustion's results show great heterogeneity. Hence, more rigorous sham control trials of acupuncture or moxibustion are necessary. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=262118, identifier CRD42021262118.